2016
DOI: 10.1108/ijm-05-2015-0076
|View full text |Cite
|
Sign up to set email alerts
|

Foreign owners and perceived job insecurity: evidence from linked employer-employee data

Abstract: Purpose The purpose of this paper is to examine the link between foreign ownership and perceived job insecurity. It takes into account that the link can depend on circumstances and type of firm. Design/methodology/approach The analysis is based on linked employer-employee data from Germany. The data enable us to account for both employee characteristics and firm characteristics. Most importantly, they allow a detailed analysis of moderating influences. Findings The estimates show that there tends to be a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…This finding provides support to the notion that foreign-owned companies offer less ISSN 1941-899X 2017 www.macrothink.org/jmr 92 secure employment because they can more easily shift production across locations and this result in employees losing their jobs (Dill & Jirjahn, 2014). In addition, 60% of employees in domestic-owned companies and 71% of employees from Chinese-owned companies indicate that due to low job security, there are few employee complaints to their employers.…”
Section: Journal Of Management Researchsupporting
confidence: 68%
“…This finding provides support to the notion that foreign-owned companies offer less ISSN 1941-899X 2017 www.macrothink.org/jmr 92 secure employment because they can more easily shift production across locations and this result in employees losing their jobs (Dill & Jirjahn, 2014). In addition, 60% of employees in domestic-owned companies and 71% of employees from Chinese-owned companies indicate that due to low job security, there are few employee complaints to their employers.…”
Section: Journal Of Management Researchsupporting
confidence: 68%
“…Foreign‐owned firms are more likely to have a works council than domestic‐owned firms (Dill and Jirjahn , Schmitt ). Employees see foreign owners as entailing greater risk and uncertainty (Dill and Jirjahn ). Thus, employees are more likely to adopt a works council, even though a council in foreign‐owned firms can only provide a minimum level of protection and aggravates conflicts with the management.…”
Section: The German Experience With Work Councilsmentioning
confidence: 99%
“…Similarly Çetindamar and Günsel (2009: 1) discusses the technological capabilities in Turkey as a developing country. Contrary to this research Dill andJirjahn (2016: 1286) focused on a developed economy in the context of Germany and found that foreign owned companies deploy technology adoption in a more efficient way than the residents do. As a result they need less labor and become more competitive respectively.…”
Section: Literature Reviewmentioning
confidence: 84%